A model no more? Debating Turkish influence in the southern neighbourhood. Issue 3 (3rd April 2022) - Aydın-Düzgit, Senem; Dandashly, Assem
ABSTRACT: Turkey has often in the past been presented by the West as a model for the countries of the Middle East and North Africa (MENA) to emulate. Drawing on interpretivist theoretical premises which conceptualize an international actor's normative agency through its external recognition in the target states and by employing frame analysis, we examine the alternative ideas of political governance associated with Turkey by the political elites in Egypt between 2011 and 2020. We show that despite the widespread debate on the relevance of the Turkish model during the Arab uprisings, its constituents as articulated by the local political actors have been heavily contested even during the democratic transition phase and in its immediate aftermath. We further contend that domestic contestation was in time replaced by the demonization of Turkey's domestic governance due to the rising antagonism between the two countries instead of a genuine engagement with governance-related norms associated with Turkey. This shows the significance of domestic politics and bilateral relations in shaping the local perceptions of a third actor as a norm diffuser in recipient countries. It also underlines the importance of unpacking the discourses in the local context in understanding whether, and if so, how third-party influence travels in a country.